Seroprevalence of Human Immunodeficiency Virus, Hepatitis B Virus and Hepatitis C Virus in Nepalgunj Medical College, Nepal - Gurung, Kishor; Poudel, T.P.; Shah, G.J.; Mishra, D. (Journal of Nepalgunj Medical College, 2018)
Introduction: Human immune deficiency viruses (HIV), Hepatitis B viruses (HBV) and Hepatitis C viruses (HCV) are the three most common chronic viral pathogens known. The viruses have common routes of transmission (such as blood and blood products, sharing needles to inject drugs and sexual activities) and similar risk factors.Aim and objective: The aim of study was to determine the seroprevalence of HIV, HBV and HCV in Kohalpur Teaching Hospital, Nepalgunj Medical College.Materials and methods: This is a descriptive hospital based study. The study was conducted at Nepalgunj Medical College, KTH, Banke. In this study, 2865 were tested for HIV, 2849 were tested for HBV and 2950 were tested for HCV from 12-01-2017 to 06-07-2017.Results: In case of HIV, 1781 (62.16%) were male and 1064 (37.84%) were female. The study revealed that in HIV reactive case was found to be 0.14% where 0.16% (3) were males and 0.09% (1) were females. In case of HBV, 1743 (61.18%) were males and 1106 (38.82%) were females. The prevalence of HBV reactive was found to be 1.65% where 1.2% (34) in male and 0.45% (13) in female. In case of HCV, 1200 (40.67%) were male and 1750 (59.33%) were female. The prevalence of HCV reactive was found to be 0.03% (1) which was only in female.Conclusion: We found that the prevalence of HIV was more predominant in males 0.16% (3). The HBV was more prevalent followed by HIV and HCV and the prevalence of HBV in male was more 1.2% (34) as compared to females 0.45% (13).